Asphaltic pavement surface analysis and its effects on the tyre-pavement friction performance. - Vieira, Tiago (2014)
This thesis analyses the tyre-pavement interaction concerning both friction and noise generation. A tribological approach was used to analyze the tyre-pavement system interaction on different conditions. Samples of pavement surfaces were extracted from a highway in the state of São Paulo, and analyzed in the laboratory. The British Pendulum Portable test was used to evaluate the pavement friction. Friction was evaluated in a systematic way, at different temperatures, with different rubbers, and at different lubricating conditions. With the different lubricating conditions, adhesion and hysteresis friction mechanisms were evaluated separately. Several tests were used to characterize the pavement surface, including the Outflow test and a Photometric technique, both with devices developed at the Pavement Technology Laboratory (LTP). With the photometric technique specific texture characteristics were evaluated and texture indicators were used in an attempt to determine whether a pavement surface is positive or negative. A previous tyre-pavement noise research data set was confronted with the surface characteristics to evaluate the effect of a positive or negative surface on noise generation. The same evaluation was used on friction, with the British Pendulum Tester data. Data verification criteria were adopted, given that many of the tests carried out in this thesis are modified from the standardized version. When the test data was successfully verified, a statistical analysis was carried out to identify the relevance of each variable on the resulting pavement performance. As a particular result, the relevance of adhesive friction was verified. The statistical analysis revealed the important role of pavement surface characteristics, specially the surface skewness. Friction and contact models were modified to account for the relevant parameters indicated by the statistical analysis.